Bentuk Host Control dan Perlindungan Hukum Bagi Penanaman Modal Asing Pasca Diterbitkannya UU Cipta Kerja di Indonesia - Anwar, Azhar Rahadiyan (Fakultas Syariah INSURI Ponorogo, 2023)
Indonesia is believed as one of the top of Emerging Market In The World. it is believed that Indonesia could be big as BRIC (Brazil, Rusia, India, China) in term of Emerging Market and Developing Economies. Unfortunately in early 2020 spesifically March 2020, COVID-19 had emerge from china which made a big panic not only for Indonesia but The World. One of the negative impact that arise from this Pandemi COVID-19 is the economic depression including the foreign direct investment. The depression of foreign direct investment affect significantly to the economic growth of a country which include Indonesia. One of the Idea of Indonesia Government as the authorize power to keep this matters in check was to simplify regulation regarding the Foreign Investment which led to the issuance of Law no. 11 of 2020. In this research, the issue that will be discussed are the the importace of Indonesia Government to control Foreign Investment.